2016
DOI: 10.1111/cea.12858
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing occupational asthma

Abstract: Summary Making an accurate diagnosis of occupational asthma (OA) is, generally, important. The condition has not only significant health consequences for affected workers, but also substantial socio‐economic impacts for workers, their employers and wider society. Missing a diagnosis of OA may lead to continued exposure to a causative agent and progressive worsening of disease; conversely, diagnosing OA when it is not present may lead to inappropriate removal from exposure and unnecessary financial and social c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 85 publications
0
59
0
13
Order By: Relevance
“…Placebo-controlled challenges were performed in a challenge chamber or with commercial allergen extracts by use of a dosimeter, in accordance with the methods described by Vanhanen et al (12). In addition, to confirm an occupational asthma diagnosis, we used peak expiratory flow monitoring at work and off work, combined with positive prick test or specific IgE results (13). Local nasal provocation tests, in accordance with the methods described by Airaksinen et al (14), were used when the patients had only upper respiratory symptoms, and the causative agent was not considered to be particularly irritating to the mucous membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Placebo-controlled challenges were performed in a challenge chamber or with commercial allergen extracts by use of a dosimeter, in accordance with the methods described by Vanhanen et al (12). In addition, to confirm an occupational asthma diagnosis, we used peak expiratory flow monitoring at work and off work, combined with positive prick test or specific IgE results (13). Local nasal provocation tests, in accordance with the methods described by Airaksinen et al (14), were used when the patients had only upper respiratory symptoms, and the causative agent was not considered to be particularly irritating to the mucous membrane.…”
Section: Methodsmentioning
confidence: 99%
“…This is in agreement with a systematic review by Beach and colleagues,23 which concluded that the diagnosis of OA in the absence of SIC should preferably be determined by a combination of NSBHR and specific sensitisation tests. Vandenplas and colleagues7 proposed NSBHR and specific SPT tests as the first step of the stepwise approach for diagnosing OA, and the American Colleague of Occupational and Environmental Medicine24 also strongly recommended these two tests in diagnosing OA.…”
Section: Discussionmentioning
confidence: 99%
“…In places without access to SIC evaluations, an estimation of the probability of occupational asthma for individuals based on their unique characteristics by this model can guide physicians at the secondary care level (specialists: ie, respirologists, occupational medicine physicians) in deciding whether: (A) they could remove workers from the exposing agents in the workplace and initiate treatment or (B) they should consider further evaluation of the clinical characteristics and order other test to confirm the diagnosis (eg, serial measurement of peak expiratory flow and/or NSBHR and/or induced sputum at work and off work) 7. Furthermore, this model could be used to assess workers with workers’ compensation claims.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations